Isolation and Identification of the Major Chemical Components of the Medicinal Plant Trachyspermum copticum (Ammi copticum) Grown in Fars Province of Iran - GHARIB NASERI, NAHID; ASHNAGAR, ALAMDAR; NOUZARI, MASOMEH (Asian Journal of Chemistry, 2010)
Extract of the fruits of Ammi copticum plant (Trachyspermum copticum), grown wildly in the Fars province of Iran, in various solvents were obtained and analyzed. GC-MS analysis of the extract and of the essential oil obtained from the fruit of the plant showed 138 components. Thymol (65 %) and linoleic acid (13.5 %) were isolated and characterized as the major chemical constituents.